Preparing Pediatric Residents for Resuscitations: Inpatient Resuscitation Scavenger Hunt - Jennifer Jackson (Association of American Medical Colleges, 2013)
Abstract Given the rarity of pediatric cardiopulmonary arrests, pediatric residents' experience in participating in resuscitations is very limited, even in large tertiary care centers. In our experience, a significant obstacle to their resuscitation performance is residents' limited awareness of which emergency supplies are available to them, where they are located, or how to access them, resulting in disorganized and inefficient leadership performance during resuscitations. We developed this scavenger hunt activity to offer an interactive and practical method of orienting residents to the emergency management supplies and other resources available to them in the inpatient clinical setting. Having a working knowledge of their supplies will increase residents' ability to more efficiently and effectively lead and participate in resuscitations. In addition, this learning activity can facilitate residents' establishment of interprofessional relationships with ancillary staff throughout the medical center as they conduct their search. We have implemented this activity with multiple resident groups during this academic year. It was clear since the beginning of our implementation that our residents enjoyed this interactive learning activity, and they have remained very enthusiastic participants. The element of competition between teams is particularly appealing to some residents, who make the activity that much more engaging for the rest of the learner group. To assess knowledge retention related to resuscitation equipment and emergency systems of care for pediatric patients in our medical center, we conducted a 6-month follow-up assessment using a 48-item quiz with scavenger hunt participants. They scored higher on the question items assessing knowledge of emergency supply location compared to controls. Based on this data, we have concluded that the scavenger hunt activity can help improve residents' knowledge of available emergency equipment and resources in their medical center compared to traditional training experiences alone.